Production in a Service Industry Using Customer Inputs: A Stochastic Model - Vany, Arthur S. De; Gramm, Wendy L.; Saving, Thomas R.; Smithson, Charles W. (The Review of Economics and Statistics, 1983)
Arthur S. De Vany, Wendy L. Gramm, Thomas R. Saving, Charles W. Smithson, Production in a Service Industry Using Customer Inputs: A Stochastic Model, The Review of Economics and Statistics, Vol. 65, No. 1 (Feb., 1983), pp. 149-153